Sex-specific sensitivity to methamphetamine-induced schizophrenia-relevant behaviours in neuregulin 1 type III overexpressing mice. (January 2021) - Chesworth, Rose; Rosa-Porto, Rossana; Yao, Sofia; Karl, Tim
Background: Gene–environment interactions contribute to schizophrenia aetiology. Neuregulin 1 is a well-established genetic risk factor for schizophrenia, and elevated expression of type III neuregulin 1 mRNA in the dorsolateral prefrontal cortex is observed in patients with a core risk haplotype. A mouse model of type III Nrg1 overexpression ( Nrg1 III tg ) possesses face and construct validity for schizophrenia; however, the sensitivity of these transgenic mice to environmental risk factors relevant to schizophrenia is unknown. Aims: To determine sensitivity of Nrg1 III tg mice to the psychostimulant methamphetamine (METH) in schizophrenia and addiction-relevant behavioural tests. Methods: We examined behavioural responses of adult male and female Nrg1 III tg mice METH (1–3 mg/kg) in schizophrenia-relevant paradigms (drug-induced locomotion, sensorimotor gating) and drug reward (conditioned place preference). Results: Male Nrg1 III tg mice were less sensitive to METH-induced stereotypies, yet showed a greater negative impact of METH on prepulse inhibition compared with wild type-like males. In contrast, female Nrg1 III tg mice were less sensitive to METH-induced locomotion than wild type-like females, while sensorimotor gating was similarly impaired by METH between the genotypes. There were no genotype differences for METH reward, or anxiety-like and exploratory behaviours. Conclusions: These results indicate that overexpression of Nrg1 type III modulates schizophrenia-relevant behaviours, and may help to explain increased sensitivity to the psychoactive effects of METH in patients with schizophrenia.